Clinician Perceptions of Timing and Presentation of Drug-Drug Interaction Alerts - Humphrey, Kate E.; Mirica, Maria; Phansalkar, Shobha; Ozonoff, Al; Harper, Marvin B. (Applied Clinical Informatics, 2020)
Objective Alert presentation of clinical decision support recommendations is a common method for providing information; however, many alerts are overridden suggesting presentation design improvements can be made. This study attempts to assess pediatric prescriber information needs for drug–drug interactions (DDIs) alerts and to evaluate the optimal presentation timing and presentation in the medication ordering process.Methods Six case scenarios presented interactions between medications used in pediatric specialties of general medicine, infectious disease, cardiology, and neurology. Timing varied to include alert interruption at medication selection versus order submission; or was noninterruptive. Interviews were audiotaped, transcribed, and independently analyzed to derive central themes.Results Fourteen trainee and attending clinicians trained in pediatrics, cardiology, and neurology participated. Coders derived 8 central themes from 929 quotes. Discordance exists between medication prescribing frequency and DDI knowledge; providers may commonly prescribe medications for which they do not recognize DDIs. Providers wanted alerts at medication selection rather than at order signature. Alert presentation themes included standardizing text, providing interaction-specific incidence/risk information, DDI rating scales, consolidating alerts, and providing alternative therapies. Providers want alerts to be actionable, for example, allowing medication discontinuation and color visual cues for essential information. Despite alert volume, participants did not “mind being reminded because there is always the chance that at that particular moment (they) do not remember it” and acknowledged the importance of alerts as “essential in terms of patient safety.”Conclusion Clinicians unanimously agreed on the importance of receiving DDI alerts to improve patient safety. The perceived alert value can be improved by incorporating clinician preferences for timing and presentation.
Keywords: drug interactions; electronic health records; health personnel alert fatigue; medication alert systems